Peran Kegiatan Kepramukaan Dalam Pengembangan Karakter Disiplin Peserta Didik Di SMP Negeri 2 Parigi Kabupaten Parigi Moutong - Firna Fitriyani; Gurnarib; Muhammad Sarib Abdul Rasak (STKIP Subang, 2026)
This study aims to analyze the role of scouting activities in developing the disciplinary character of students at SMP Negeri 2 Parigi, Parigi Moutong Regency, Indonesia. The study is motivated by the importance of character education, particularly discipline, in shaping students' attitudes, behaviors, and sense of responsibility both in the school environment and in their daily lives. Scouting is considered one of the most effective extracurricular activities for instilling disciplinary values through structured, continuous, and character-oriented programs. This research employed a qualitative approach using a descriptive case study design. Data were collected through observation, interviews, and documentation. The research participants consisted of the school principal, scout leaders, and students who actively participated in scouting activities at SMP Negeri 2 Parigi. The findings reveal that scouting activities play a significant role in fostering students' disciplinary character. Disciplinary values are developed through regular training sessions, marching drills, flag ceremonies, camping activities, educational games, and group-based tasks that emphasize punctuality, responsibility, cooperation, and adherence to rules. The successful implementation of scouting activities is supported by the commitment of the school principal, the competence of scout leaders, parental support, and the availability of adequate facilities and infrastructure. However, several challenges remain, including limited facilities, insufficient training time, budget constraints, and the low level of discipline awareness among some students. The study concludes that scouting activities are an effective strategy for strengthening discipline-based character education in schools. Therefore, sustained commitment from all stakeholders is essential to optimize scouting programs as an integral component of students' character development.